2021
DOI: 10.1177/00187208211061938
|View full text |Cite
|
Sign up to set email alerts
|

Designing Combinations of Pictogram and Text Size for Icons: Effects of Text Size, Pictogram Size, and Familiarity on Older Adults’ Visual Search Performance

Abstract: Objective This study aimed to determine suitable combinations of text and pictogram sizes for older adults and investigated the visual prioritization of pictogram versus text. Background Icons have become an indispensable part of application (app) design. Pictogram size and text size of icons influence the usability of apps, especially by aged users. However, few studies have investigated the influences of different pictogram and text size combinations on readability, legibility, and visual search performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 50 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…This dominant effect of SIs on visual searching was also shown by Leung et al [10]. Additionally, text may help users to better understand the semantic meaning of the icons [22,39]. The combination of icon and text provided redundant information, making it easier for the users to establish substantive connections between new information This study showed that among the four types of icons, i.e., FI, SI, FI + text, and SI + text, all the older adults had the best visual search, processing, search response time, and search accuracy for SI + text, followed by FI + text and SIs, showing the poorest outcomes when searching for FIs.…”
Section: Fixation Duration (Fd)supporting
confidence: 57%
See 1 more Smart Citation
“…This dominant effect of SIs on visual searching was also shown by Leung et al [10]. Additionally, text may help users to better understand the semantic meaning of the icons [22,39]. The combination of icon and text provided redundant information, making it easier for the users to establish substantive connections between new information This study showed that among the four types of icons, i.e., FI, SI, FI + text, and SI + text, all the older adults had the best visual search, processing, search response time, and search accuracy for SI + text, followed by FI + text and SIs, showing the poorest outcomes when searching for FIs.…”
Section: Fixation Duration (Fd)supporting
confidence: 57%
“…Regarding the effect of icon types on the search behavior of older adults, several recent studies focused on icon characteristics, such as semantic distance, visual complexity, and familiarity, and how they influence the search performance of older adults [21][22][23][24]. Studies have revealed that icons with high visual complexity impair the search performance of older adults (longer reaction times and more errors) [24], whereas icons with closer semantic distance reduce these effects [21].…”
Section: Introductionmentioning
confidence: 99%
“…Fixation duration refers to the process of maintaining a visual gaze toward a single location and indicates that a person is collecting information about that spot (Ponce and Mayer, 2014). Specifically, eye fixations are events in Mobile learning efficiency which the eyes remain relatively still, indicating an area that is of interest to the user or is difficult to understand as its elements are more noticeable or more important (Hou and Hu, 2021). Previous studies have suggested that the relationships between eye movement and mind-visual processing patterns reflect the cognitive strategies used by users and that cognitive load can be inferred from eye-movement data (e.g.…”
Section: Cognitive Loadmentioning
confidence: 99%
“…However, future studies should explore more font size options due to the constant increase in the size of mobile displays, which has been evident over the past decade. Research has been done on font size, line spacing and word spacing to determine suitable font sizes for better legibility, readability and reading speed (Epelboim et al, 1994 ; Rayner et al, 1998 ; Bernard et al, 2001 ; Alotaibi, 2007 ; Wang et al, 2009 ; Hou and Hu, 2022 ).…”
Section: Related Workmentioning
confidence: 99%